Pengembangan Sistem Informasi Point of Sales berbasis Web menggunakan Framework Laravel (Studi Kasus: Meetup Station) - Gladys Wahyu Khairunnisa; Issa Arwani; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Meetup Station is an SME that has operated in Tuban since 2020 and focuses on culinary business especially fast served food and beverages. In the present, they still use physical sharing books to record transactions and manage the accounting manually that leads to so much inconsistent data. To solve that problem, a point of sales system needs to be implemented to help manage and record transactions easily. The point of sales system will be developed using waterfall method, PHP Laravel 8 framework and PostgreSQL database. From the quality assurance test results, all functional requirements have been tested 100% valid and the system has been displayed well in 8 different browsers and responsive for many kinds of display such as PC monitor, tablet, and smartphone.